THE RELEVANCE OF ROOT CANAL ISTHMUSES IN ENDODONTIC REHABILITATION - Alexandru Andrei Iliescu; Mihaela Georgiana Iliescu; Cristina Coralia Nistor; Iulia Roxana Marinescu; Irina Maria Gheorghiu; Tiutiucă Carmen; Focșăneanu Sergiu Ciprian; Doriana Agop Forna (Romanian Society of Oral Rehabilitation, 2023)
Though important in current endodontic practice the issue of root canal isthmuses is usually overlooked due to the inefficient means of imagistic identification in clinical setting and appropriate treatment approach. Canal isthmuses are still the dark face of the endodontic system regarding the efficacy of conventional orthograde treatment of the root canals especially in the roots having two or more main canal where these anatomies are chiefly located. Advances in CBCT equipments with small field of image capture (FOV) open a window to an improved treatment outcome.